A Simulation and Experimental Investigation of the Thermal Characteristics of Refractory Bricks Produced Using Fireclay and Agroforestry Wastes - Obidiegwu, Eugenia Obiageli; Esezobor, David Ehigie; Mgbemere, Henry Ekene; Odili, Chiosa Cletus (Journal of Casting & Materials Engineering, 2022)
Manufacturing and processing industries usually consume large quantities of materials and energy in the course of their operations. The energy supplied for high-temperature processes are used partially for the actual technical process and between 30 to 40% of the energy escapes through the walls of the reactor into the atmosphere, leading to a high degree of thermal inefficiency and fuel consumption. This paper studies the thermal behaviour of insulating refractory bricks produced from a blend of fireclay and agroforestry wastes. The fireclays used were obtained from Ukpor deposit in Anambra State (Latitude 5.95°N, Longitude 6.92°E), Osiele deposit in Abeokuta, Ogun State (Latitude 7.18°N, Longitude 3.45°E) and Kankara Katsina State (Latitude 11.93°N, Longitude 7.41°E), all of which are in Nigeria. Samples were prepared with various weight percentages (60–100 wt.%) clays and (0–40 wt.%) of agroforestry waste, with grain sizes between 212 and 600 µm. Raw materials and the developed refractory bricks were characterised using appropriate standard techniques. The chemical, mineralogical constituents and phases present in the microstructure were examined. Physical and thermo-mechanical properties were investigated. The insulating refractory bricks developed have porosity of 78.83% , cold crushing strength (CCS) 3.144 kN/m2 and thermal conductivity 0.04–0.046 W/(m∙K) that compare favourably with imported bricks 75–85%, 2.756 kN/m2 and 0.049 W/(m∙K) in both physical, mechanical and thermal properties respectively. The reason is that the agroforestry waste used (coconut shell), served to create the pores that improve insulation after burning. Also the ash that remains serves as reinforcement to improve the mechanical properties. The thermal behaviour of the bricks was studied using Finite Element Method and shows a strong correlation with the experimental findings. This indicates that the produced insulating bricks have the thermal properties required for insulation of furnaces.